Different Resistance to UV-B Radiation of Extracellular Polymeric Substances of Two Cyanobacteria from Contrasting Habitats - Song, Wenjuan; Zhao, Chenxi; Zhang, Daoyong; Mu, Shuyong; Pan, Xiangliang (Frontiers in Microbiology, 2016)
The effects of UV-B radiation (UVBR) on photosynthetic activity (Fv/Fm) of aquatic Synechocystis sp. and desert Chroococcus minutus and effects on composition and fluorescence property of extracellular polymeric substances (EPS) from Synechocystis sp. and Chroococcus minutus were comparatively investigated. The desert cyanobacterium species C. minutus showed higher tolerance of PSII activity (Fv/Fm) to UVBR than the aquatic Synechocystis sp., and the inhibited PSII activity of C. minutus could be fully recovered while that of Synechocystis sp. could be partly recovered. UVBR had significant effect on the yield and biochemical composition of EPS of both species. Protein-like and humic acid-like substances were detected in EPS from Synechocystis sp., and protein-like and phenol-like fluorescent compounds were detected in EPS from C. minutus. Proteins in EPS of desert and aquatic species were significantly decomposed under UVBR, and the latter was more easily decomposed. The polysaccharides were much more resistant to UVBR than the proteins for both species. Polysacchrides of Synechocystis sp. was degraded slightly but those of C. minutus was little decomposed. The higher tolerance to UVBR of the desert cyanobacterium can be attributed to the higher resistance of its EPS to photodegradation induced by UVBR in comparison with the aquatic species